Identification of adolescents and young adults' preferences and priorities for future cancer treatment using a novel decision‐making tool. Issue 1 (5th October 2020) - Snaman, Jennifer M.; Helton, Gabrielle; Holder, Rachel L.; Revette, Anna; Baker, Justin N.; Wolfe, Joanne
Abstract: Background: Adolescents and young adults (AYAs) with cancer receive high‐intensity care and experience significant symptoms at the end of life. As novel cancer‐directed therapies increase, AYAs with advanced cancer may face multiple treatment options, each with unique risk/benefit profiles. To augment the AYAs' voice in the decision‐making process, we developed MyPref, an adaptive conjoint analysis‐based tool. Procedure: We conducted a three‐staged pilot study of MyPref utilizing an exploratory intervention mixed methods design. AYAs and their identified parent or trusted person (PTP) completed MyPref and received a summary of their preferences for nine treatment‐related factors. Participants later engaged in semi‐structured interviews to further explore their experience with MyPref . Responses to free text questions and interviews were analyzed using qualitative techniques. Results: Fifteen AYAs with advanced cancer and seven PTPs participated in the pilot. While most participants identified time until cancer grows, quality of life, and side effects to be the most important factors when considering a future treatment, preferences were highly varied. Notably, MyPref ‐calculated preferences differed from initial rank order, and participants indicated that calculated preferences were accurate in follow‐up interviews. Conclusion: The MyPref ‐calculated preferences varied by individual and differed from initial rank ordering. Additionally, there was variability in how individuals defined and prioritized treatment‐related factors. This novel tool may be a useful way to engage AYAs and their PTPs in discussions around preferences for treatment and prepare AYAs for future decision making. We plan to evaluate this tool longitudinally to evaluate the impact on actual treatment decisions.